Anatomical head model to measure impact force transfer through the head layers and their displacement - Falland-Cheung, L.; Neil Waddell, J.; Li, K. C.; Tong, D. C.; Brunton, P. A. (Journal of Concussion, 2018)
When the human head is subjected to blunt force impact, there are several mechanical responses that may result from the forces involved, including absorption of impact forces through the various layers of the head. The purpose of this study was to develop an anatomical head model to measure force transfer through the various head layers and their displacement when subject to short-duration high-velocity impacts. An anatomical head model was constructed using previously validated simulant materials: epoxy resin (skull), polyvinyl siloxane (scalp), agar/glycerol/water (brain) and modified intravenous fluid for the cerebrospinal fluid. An array of accelerometers (4 mm × 4 mm × 1.45 mm) was incorporated into the various layers of the head to measure forces in x- (anterior/posterior), y- (left/right) and z- (up/down) axis. All sensors were connected to a signal conditioning board and USB powered data loggers. The head model was placed into a rigid metal stand with an optical sensor to trigger data capturing. A weight (750 g) was dropped from a height of 0.5 m (n= 20). Impact forces (z-axis) of 1107.05 N were recorded on top of the skin, with decreasing values through the different layers (bottom of skin 78.48 N, top of skull 319.82 N, bottom of skull 87.30 N, top and centre of brain 47.09 N and base of brain 78.41 N. Forces in the x- and y-axes were similar to those of the z-axis. With the base of the brain still receiving 78.41 N, this highlights the potential danger of repetitive impact forces to the head. Upon impact the layers of the head are displaced in the x-, y- and z-direction, with the highest values shown in the z-axis. In conclusion, this study identified the importance of considering short-duration high-intensity impacts to the head and their effect on underlying tissues.